Are We Ready for Newborn Genetic Screening? A Cross-Sectional Survey of Healthcare Professionals in Southeast China - Xian Wu; Yuqi Yang; Lingna Zhou; Wei Long; Bin Yu (Frontiers Media S.A., 2022)
ObjectivesTo understand the knowledge, attitude, willingness, and ability of healthcare professionals working in newborn screening (NBS) centers regarding newborn genetic screening (nGS).MethodsThe questionnaire consisted of four sections with 27 questions and the data were collected by the WJX platform. All participants accessed the questionnaire by scanning a specific QR code with their mobile phones. Two researchers independently completed the summary and analysis.ResultsA total of 258 valid questionnaires were collected from 43 NBS centers in six provinces of southeast China. In total, 209 (81.01%) participants were interested in nGS, and almost all participants (97.67%) thought that nGS was necessary in China. About 89.53% of participants thought that it could be used to effectively expand the diseases that could be screened, but 72.87% also worried about the inability to provide genetic counseling. About 55.34% suggested that nGS and tandem mass spectrometry (TMS) screening could be applied in a unite screening mode. The higher the institution and personal education levels, the higher the interest healthcare professionals displayed toward nGS. However, they also showed greater concern about the inability to provide genetic counseling and ethical issues. If a center had engaged in TMS screening, its staff would have been more likely to believe that nGS had great advantages. In addition, most participants had ethical concerns, such as "the psychological burden caused by carrying information regarding adult morbidity risk."ConclusionMost participants were interested and considered nGS necessary. The inability to provide genetic counseling may be the primary impediment to clinical practice. Three important influencing factors were level of education, institution level, and engagement in TMS screening.